Implications of the Dual Crisis of Terrorism and Corruption on The Economic Development in Iraq: A Comparative Analysis - Makki Hamzah, Abbas; Ibrahim Mahdi Alzurfi, Ahmed; Kamil Baiway, Ali; Nima Bekheet, Heider; Abdulkhidhr AL.Musawy, Hanan (International Journal of Psychosocial Rehabilitation, 2020)
Recently, researchers and experts concerned with economic affairs have increased interest in managing the returns of natural resources and how they can best be used to achieve economic prosperity and prosperity for people in developed countries. Most developed countries have devised different strategies and models for successful management of these riches. Accordingly, some suggest a model for establishing sovereign funds under various names to preserve these fortunes for contemporary generations and future generations in a way that contributes to achieving growth and development of the economy and raising living standards and enhancing the welfare of its residents. Meanwhile, others suggest a direct distribution model for the income from natural and oil resources, especially among the population, which contributes to improving living standards and the well-being of individuals. Many countries have started applying this model. In our world today, the American state of Alaska is the most famous application and success, followed by the Canadian province of Alberta, which used the model of direct distribution of oil wealth to the population. Regardless of ideas and opinions, the idea of establishing what might be called (the Iraqis fund) represents the best, efficient and fair way to ensure the Iraqi population enjoy the wealth, especially after the governments that ruled after the change in (2003) failed to provide the most basic services and rights to this country. Besides, the economic and social benefits that can accrue from supporting the consumer's capabilities and the agreement of individuals can be strengthened, which in turn will form the core of economic activity and its prosperity.